2012
DOI: 10.1001/archdermatol.2012.125
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Toxic Effects Associated With Vemurafenib and Inhibition of the BRAF Pathway

Abstract: Background: The development of a novel BRAF inhibitor, vemurafenib, has been associated with impressive tumor regression in patients with BRAF-positive stage IV melanoma. In the phase 3 clinical trials, dermatologic toxic effects associated with vemurafenib were described, namely, the development of eruptive squamous cell carcinomas. Herein, 3 cases are presented that highlight the development of squamous cell carcinomas and other cutaneous sequelae that have not been previously reported and are reminiscent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 28 publications
4
58
0
2
Order By: Relevance
“…5). Patients who develop cutaneous tumors frequently acquire multiple primary lesions, which can affect entire limbs or chest (29,30), a phenotype consistent with an infectious disease. Furthermore, the pathology of tumors is also not limited to cSCC and keratoacanthoma.…”
Section: Discussionmentioning
confidence: 99%
“…5). Patients who develop cutaneous tumors frequently acquire multiple primary lesions, which can affect entire limbs or chest (29,30), a phenotype consistent with an infectious disease. Furthermore, the pathology of tumors is also not limited to cSCC and keratoacanthoma.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BRAF inhibitor was found to have radio sensitization effect (132,133). However, the radiosensitization effect of BRAF inhibitor also increased the risk of skin toxicities with radiation (133)(134)(135)(136). Due to the minimum skin dose from SRS, several studies that evaluated BRAF inhibitor with SRS for patients with brain metastases reported favorable outcome (137)(138)(139).…”
Section: Rt With Concomitant Agentsmentioning
confidence: 99%
“…50 Interestingly, this paradoxical activation has been proposed as an etiologic factor in the development of squamous cell carcinomas of the skin, which may occur in patients treated with BRAF inhibitors. 51,52 …”
Section: Issues In Specific Tumor Typesmentioning
confidence: 99%